Diffusion between interstitial sites in the hexagonal C14 AB2 structure - Sholl, Colin A. (Diffusion Fundamentals, 2005)
An exact algebraic expression is derived for the diffusivity of H between interstitial sites in the hexagonal C14 AB2 structure in terms of the jump rates between the sites. The expression is valid in the low concentration limit. The theory is applied to obtaining H jump rates from diffusivity data for ZrCr2Hx.